Islamic Guidance and Counseling Program of Marriage and Family Self Readiness for FAI UIKA Bogor Students - Gemi Wulandari; Abdul Hayyie Al Kattani (Prophetic guidance and counseling journal, 2020)
Dating activity is widespread among students even to the point of having an abusive relationship. Dating is an activity to find a partner that is not recommended in Islam. This study aims to find out how the implementation of Islamic guidance and counseling programs of marriage and family self-readiness for FAI UIKA Bogor students. This research was conducted in the Faculty of Islamic Religion (FAI) of the University of Ibn Khaldun (UIKA) Bogor. The research method is descriptive qualitative with a field research approach. Data collection and analysis are collected from interview, observation and documentation techniques. The primary sources in this study is the coordinator and person in charge of guidance and counseling services at FAI UIKA and three students who were married. While the secondary data sources are the Dean, Deputy Dean, Lecturer, and Chair of BEM FAI, as well as three unmarried FAI students. Based on the results of the interviews, observations and documentation it could be concluded that the readiness program of marriage and family at FAI UIKA is implemented as an effort to overcome various cases of dating behavior among FAI UIKA students. The program implementation consists of four components: basic guidance services, responsive services, individual planning, and system support.AbstrakKegiatan pacaran tersebar luas di kalangan mahasiswa bahkan sampai pada titik hubungan yang melecehkan. Pacaran adalah kegiatan mencari jodoh yang tidak dianjurkan dalam Islam. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi program bimbingan dan konseling Islam perkawinan dan kesiapan diri keluarga pada mahasiswa FAI UIKA Bogor. Penelitian ini dilaksanakan di Fakultas Agama Islam (FAI) Universitas Ibn Khaldun (UIKA) Bogor. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan penelitian lapangan. Pengumpulan dan analisis data dikumpulkan dari teknik wawancara, observasi dan dokumentasi. Narasumber utama dalam penelitian ini adalah koordinator dan penanggung jawab layanan bimbingan dan konseling di FAI UIKA dan tiga orang mahasiswa yang sudah berkeluarga. Sedangkan sumber data sekunder adalah Dekan, Wakil Dekan, Dosen, dan Ketua BEM FAI, serta tiga mahasiswa FAI yang belum menikah. Berdasarkan hasil wawancara, observasi dan dokumentasi dapat disimpulkan bahwa program kesiapan pernikahan dan keluarga di FAI UIKA dilaksanakan sebagai upaya untuk mengatasi berbagai kasus perilaku pacaran di kalangan mahasiswa FAI UIKA. Pelaksanaan program terdiri dari empat komponen: layanan bimbingan dasar, layanan responsif, perencanaan individu, dan dukungan sistem.